Determining the Pressure of Tight Pants on Human Body by Numerical Simulation Method - Nguyen, Quoc Toan; Dinh, Van Hai; Phan, Thanh Thao (Old Journal, 2018)
This paper focuses on the determination of wearing pants-induced pressure on young female legs by using a numerical simulation method. A 3D biomechanical model for simulating the pressure magnitude and distribution is constructed based on the actual geometry of a female leg obtained from 3D reconstruction of computerized tomography (CT) scan images. The biomechanical solid leg model consists of three main components: skin, bones, and soft tissues. A shell model is also built for the trouser leg. The mechanical properties of bones are assumed to be a rigid material, while skin and soft tissues are considered as homogeneous linear elastic materials. Material properties of trouser fabrics are experimentally determined through tensile tests. The commercial finite element program ABAQUS is employed to simulate the pressure distributions and biomechanical responses induced by wearing pants at three typical cross-sections of legs. In addition, experiments for measurement of pressure distribution are further carried out. A careful comparison between simulation and experimental results shows a good qualitative and quantitative agreement, which suggests that the proposed biomechanical model can be used to predict, analyze, and determine pressure of tight-fit cloth on human body. The present study thus provides a reliable and efficient way for clothing design that satisfy the comfort conditions in use.